PENINGKATAN HASIL BELAJAR IPS PADA MATERI JENIS USAHA EKONOMI MELALUI MODEL PEMBELAJARAN PROJECT BASED LEARNING SISWA KELAS V DI SDN CIJOHO - Elia Kurniati; Aiman Faiz; Nurkholis; Rohadi (STKIP Subang, 2023)
The type of research used in this research is classroom action research (CAR), which consists of two cycles. In each cycle includes planning, implementation, observation and reflection. This stage is a cycle that takes place repeatedly and is carried out with the same steps and is focused on the project based learning (PjBL) model. The data collection technique used is observation while students follow the learning process and use tests in the form of questions carried out at the end of the cycle as well as documentation during learning activities. Data analysis techniques used are quantitative and qualitative. The results of this study indicate an increase in IPS learning outcomes through the Project Based Learning (PjBL) learning model in each cycle. This improvement in learning outcomes can be seen through the cycles that have been carried out. In cycle I, student learning outcomes reached 66.6% of 24 students and only 16 students completed. Furthermore, in cycle II there was an increase with learning outcomes reaching 83.3% completeness and only 4 students who did not complete. The conclusion from this study is that there is an increase in social studies learning outcomes in the material types of economic enterprises through the project based learning (PjBL) learning model for fifth grade students at SDN Cijoho.